Effects of chemotherapy on innate and adaptive immune responses - Biller, Barbara J., author; Dow, Steve, advisor (Colorado State University. Libraries, 2007)
Chemotherapy has historically been viewed as immunosuppressive; however studies suggest that some chemotherapeutic agents possess immunostimulatory effects. Despite the promise offered by new treatment modalities such as immunotherapy, novel therapies appear most effective when used in combination with traditional treatments such as chemotherapy. Therefore, there is considerable interest in the identification of chemotherapeutics that can be synergistically combined with cancer immunotherapy. Little is known, however, concerning the immunomodulatory effects of chemotherapy on many aspects of immunity.

Therefore, we evaluated the effects of common chemotherapy drugs on dendritic cells and lymphocytes, two cell types critical to the generation of effective immune responses. In addition, because regulatory T cells are known to directly suppress antitumor immunity in human cancer patients, we developed an assay to identify canine regulatory T cells and initiated the study of this T-cell subset in dogs.

Studies of the effects of chemotherapy on lymphocytes were conducted in pet dogs with lymphoma or osteosarcoma. Through evaluation of lymphocyte subsets and humoral antibody responses before, during, and after chemotherapy, we found that chemotherapy had little impact on adaptive immune responses. Compared to healthy dogs, however, tumor-bearing dogs had abnormally low T-cell numbers and increased numbers of regulatory T cells. Our findings demonstrate the minimal impact of chemotherapy on lymphocyte numbers, suggesting that chemotherapy itself is not likely to interfere with induction of cell-mediated antitumor responses. However, underlying malignancy could play a role in suppression of antitumor immunity.

The impact of chemotherapy on dendritic cell function was assessed in mice. These studies demonstrated that the drug doxorubicin stimulated multiple aspects of dendritic cell function, including costimulatory molecule expression and antigen presentation. In mice with melanoma, administration of doxorubicin led to increased numbers of mature dendritic cells within tumor tissues and tumor-draining lymph nodes. These experiments suggest that doxorubicin is a promising candidate for combination with tumor-specific immunotherapy.

The studies presented here provide important insight into the effects of chemotherapy on immunity in healthy and tumor-bearing animals. Most importantly, they set the stage for future work investigating combinations of chemotherapy and immunotherapy towards the development of more effective treatments for cancer.
Keywords: adaptive immune responses; chemotherapy; dendritic cells; immune response; innate immunity; lymphocytes; cellular biology; immunology